In-situ Raman characterization of SOFC anodes - Maher,RC; Offer,G; Brandon,NP; Cohen,LF (Materials Research Society Symposium Proceedings, 2012)
Solid oxide fuel cells (SOFCs) have many advantages when compared to other fuel cell technologies, particularly for distributed stationary applications. As a consequence they are becoming ever more economically competitive with incumbent energy solutions. However, as with all technologies, improvements in durability, efficiency and cost is required before they become feasible alternatives. Such improvements are enabled through improved understanding of the critical material interactions occurring during operation. Raman spectroscopy is a noninvasive and non-destructive optical characterization tool which is ideally suited to the study of these critical chemical processes occurring within operational SOFCs. In this paper we will discuss advantages of using Raman characterization for understanding these important chemical processes occurring within SOFCs. We will present the specific examples of the type of measurement possible and discuss the direction of future research. © 2012 Materials Research Society.